In vitro cellular responses to Neospora caninum glycosylphosphatidylinositols depend on the host origin of antigen presenting cells. (July 2019) - Débare, Héloïse; Schmidt, Jörg; Moiré, Nathalie; Ducournau, Céline; Acosta Paguay, Yoshuá D.; Schwarz, Ralph T.; Dimier-Poisson, Isabelle; Debierre-Grockiego, Françoise
Graphical abstract: Highlights: Glycosylphosphatidylinositols of Neospora caninum induce Th1 cytokines in mouse cells. Glycosylphosphatidylinositols of Neospora caninum induce IL-10 in bovine cells. Glycosylphosphatidylinositols of Neospora caninum signal through Toll-like receptors. Glycosylphosphatidylinositols of Neospora caninum are excreted in culture supernatant. Anti-glycosylphosphatidylinositol antibodies are detected in serum of infected mouse. Abstract: Neosporosis due to Neospora caninum causes abortions in farm animals such as cattle. No treatment and vaccine exist to fight this disease, responsible for considerable economic losses. It is thus important to better understand the immune responses occurring during the pathogenesis to control them in a global strategy against the parasite. In this context, we studied the roles of N. caninum glycosylphosphatidylinositols (GPIs), glycolipids defined as toxins in the related parasite Plasmodium falciparum . We demonstrated for the first time that GPIs could be excreted in the supernatant of N. caninum culture and trigger cell signalling through the Toll-like receptors 2 and 4. In addition, antibodies specific to N. caninum GPIs were detected in the serum of infected mice. As shown for other protozoan diseases, they could play a role in neutralizing GPIs. N. caninum GPIs were able to induce the production of tumour necrosis factor-α, interleukin(IL)-1β and IL-12 cytokines by murine macrophages and dendritic cells. Furthermore, GPIs significantly reduced expression of major histocompatibility complex (MHC) molecules of class I on murine dendritic cells. In contrast to murine cells, bovine blood mononuclear cells produced increased levels of IFN-γ and IL-10, but reduced levels of IL-12p40 in response to GPIs. On these bovine cells, GPI had the tendency to up-regulate MHC class I, but to down-regulate MHC class II. Altogether, these results suggest that N. caninum GPIs might differentially participate in the responses of antigen presenting cells induced by the whole parasite in mouse models of neosporosis and in the natural cattle host.